PERAN REKOMENDASI FINANCIAL ACTION TASK FORCE (FATF) DALAM PENANGANAN PENDANAAN TERORISME DI INDONESIA - Putri, Yuliana Andhika Risang; Hanura, Marten; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2015)
Financing factor is the most important aspects to the ongoingactivities of terrorism. FATF was established to implementinternational standards and promote effective measures in dealingwith financial crimes such as money laundering and financingterrorism,and had set up series of recommendations. FATF hasconcerning with Indonesia since Indonesia have been blacklisted byFATF related to financing terrorism. This research uses qualitativemethod with descriptive type. The analysis in this research usesInternational Society Centric Constructivism supported by MarthaFinnemore which assumes that the norm offered by internationalorganizations may affect countries to adopt these norms as theirnational policy. The regime approach is also used in this study,through the basic assumption that international organization plays arole as regulator that require member states to submissive it.Indonesia has national interest in the international world, and this isthe background for Indonesian government to comply with andimplement the FATF nine special recommendations in handling thefinancing of terrorism.The results of this study concluded that byimproving compliance and implementation of the FATFrecommendations, Indonesia could preserve the security and stabilityof the country's efforts to combat the financing terrorism and raisingintegrity in the international community.